Model-driven engineering and software development : 6th International Conference, MODELSWARD 2018, Funchal, Madeira, Portugal, January 22-24, 2018, Revised selected papers /: 6th International Conference, MODELSWARD 2018, Funchal, Madeira, Portugal, January 22-24, 2018, Revised selected papers. (2019) - Unknown
No abstract available